INFLUENCE OF MOTIVATION AND STAFF MANAGERIAL ACTIVITIES ON THE PERFORMANCE LEADER STAFF OFFICE DINAS PEKERJAAN UMUM KABUPATEN SAMPANG - S. Anugrahini Irawati; Bambang Sudarsono (Eco-Entrepreneur, 2015)
The prime leader function is to direct the employees toward their daily assignment particularly to get the performance wish for. The research within “Influence of Motivation And Staff Managerial Activities on The Performance Leader Staff Office Dinas Pekerjaan Umum Kabupaten Sampang”. Subsequent to analysis as untied in the discourse section, can be fetched the conlude. The basically, motivation and leader manajerial activity that established such admittance, duty, rensponsibility, chance to advance, emotion intelligence, social intelligence, and learn ability in the circle. The Office of Dinas Pekerjaan Umum as observed by calculatinh result is good. To based on infencial statistic analysis result, in fact, all variables: admitance (X1), job itself (X2), responsibility (X3), chance to advance (X4), emotion intelligence (X5), social intelligence (X6), and learning ability (X7); either along with or parcial have a significan effect toward employee performance in the Office of Dinas Pekerjaan Umum Kabupaten Sampang, either by empiric or teoritic said that the variable of admitance (X1), job itself(X2), responsibility (X3), chance to advance (X4), emotional intelligence (X5), social intelligence (X6), and learning ability (X7) to become factor that can improve the employee performance. Even though in the research, existed the other variable outside the research such work circle, insentive, and partner.